PP.LB03.19: POSTPRANDIAL AND LONG-TERM EFFECTS OF CONSUMPTION OF LOW GLYCEMIC INDEX AND LOW GLYCEMIC LOAD DESSERTS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS. (June 2015) - Argiana, V.; Kanellos, P.; Makrilakis, K.; Eleftheriadou, I.; Tsitsinakis, G.; Kokkinos, A.; Perrea, D.; Tentolouris, N.
Abstract : Objective: The aim of the present study was to examine the postprandial and long-term effects of consumption of desserts with low glycemic index (GI) and low glycemic load (GL), as part of a balanced hypo-caloric diet, on anthropometric and biochemical parameters in patients with type 2 diabetes mellitus (T2DM). Design and method: A total of 61 subjects with T2DM were randomly assigned to the intervention (n = 30) or to the control group (n = 31). Both groups followed the same hypo-caloric (-500 kcal) diet for 12 weeks. Consumption of 4 portions of low GI/GL desserts/ week was included in the diet in the intervention group while 1 portion of a favorite usual sweet/ week was allowed to be consumed in the control group. A meal tolerance test was performed at the end of the study to assess acute metabolic responses. Results: Thirty subjects in the control and 28 subjects in the intervention group completed the trial. Significant decreases (p < 0.001) in body weight, waist and hip circumferences, BMI, systolic and diastolic blood pressure were observed in participants in intervention group. The difference between the two groups at the end of the trial was found to be significant for hip circumference (p = 0.030). Serum fasting glucose, serum fasting insulin and HbA1c concentrations as well as HOMA-IR and γ-GT were decreased in the intervention group (p = 0.013, p = 0.031, p = 0.005, p = 0.013 and p = 0.007, respectively), but no significant differences were observed between the two groups at week 12. C-reactive protein was reduced in the intervention (p = 0.020) while HDL cholesterol was reduced in the control group (p = 0.018); the reductions were significantly different at the end of the trial (p = 0.007 for both parameters). No significant changes were observed in the other plasma lipids, uric acid, leptin, adiponectin, and interleukin-6 in either study group. The postprandial glycemic response was significantly lower after ingestion of low GI/GL dessert compared to the usual dessert (p < 0.001). Conclusions: Consumption of desserts with low GI/GL in a balanced hypo-caloric diet has a positive impact on anthropometric and metabolic parameters in patients with T2DM.